Frequency of acute breathing infections in children and adolescents with asthma from Pinar del Río - Odalys Orraca Castillo; Emilio Navarro Palmera; William Quintero Pérez; Tatiana Margarita Blanco Valdés; Leovaldo René Rodríguez Machín (Centro Provincial de Información de Ciencias Médicas, 2018)
An analytic epidemiologic, of cases and controls study in exploratory phase, aimed at determining if the frequency of breathing infections in children and adolescents with asthma from Pinar del Río exceeded the one observed in those that didn't present that disease, was carried out from July, 2014 to June, 2015. Two groups of 585 members each one were conformed for that purpose, that is to say a control for each case. After having processed the information, there was a prevalence of the male sex, while, the common cold was the infection that affected with higher frequency fundamentally those patients aged 5-9. Also, it was emphasized an increment of the risk from suffering--in order of frequency--disorders, such as common cold, acute tonsillitis and pneumonia, bronchopneumonia, as well as interstitial pneumonia.